2000
DOI: 10.1190/1.1438744
|View full text |Cite
|
Sign up to set email alerts
|

A brief overview of seismic air-gun arrays

Abstract: This article summarizes salient points one must know about seismic airgun arrays to discuss seriously how they might affect marine life. It is by no means exhaustive but tries to be thorough enough without being too involved to deter the general reader.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 0 publications
1
68
0
1
Order By: Relevance
“…For the Nordkappbanken experiment, we did not have hydrophone observations and simply used the same source level of 250.5 dB as in the Vesterålen case. Note that no difference in directionality was assumed and that the air-gun configuration was slightly different; based on the data in Table 1 and following Caldwell and Dragoset (2000), we may expect a difference of 1.3 dB re 1 Pa 2 (1 s). Using eq.…”
Section: Simple Noise Propagation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For the Nordkappbanken experiment, we did not have hydrophone observations and simply used the same source level of 250.5 dB as in the Vesterålen case. Note that no difference in directionality was assumed and that the air-gun configuration was slightly different; based on the data in Table 1 and following Caldwell and Dragoset (2000), we may expect a difference of 1.3 dB re 1 Pa 2 (1 s). Using eq.…”
Section: Simple Noise Propagation Modelmentioning
confidence: 99%
“…Note that Carey (2006) uses the notation E x as opposed to E. Note also that source levels are different than the actual exposure level close to the air-gun (Caldwell and Dragoset 2000), since the signals from the individual air-guns interact and create the combined and focused pulse in the far field. Consequently, the EFSL serves only as a reference when estimating the levels at a distance and are not valid at short range.…”
Section: Simple Noise Propagation Modelmentioning
confidence: 99%
“…During a typical seismic survey, each airgun fires sharp, broadband, low-frequency bursts of gas every 10 to 30 s towards the seabed (e.g. Greene & Richardson 1988, Dragoset 1990, 2000, Caldwell & Dragoset 2000. In many instances, we found that the time be tween seismic pulses was occupied by a series of multiple arrivals of the same reverberated pulse immediately following the original (Guerra et al 2011(Guerra et al , 2016, thus inundating the soundscape with near-continuous elevated noise levels.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition schema with the towed land streamer is similar to technique on which the marine surveys was primarily based [3,4,6,9]. In contrast to the continuous movement of marine survey systems, the operational procedure of the towed land streamer is based on a "excitation technique at a standstill" tactic with some projected acquisition step [17,7,8,14,15].…”
Section: Brief Description Of Device Application Proceduresmentioning
confidence: 99%
“…Researchers for over two decades attempted to find a way to tow long receiver spreads across the ground surface in a way similar to marine sea-streamers. This would allow to transfer efficiency of seismic surveying to land [2], [3], [8] Shear wave land streamers were also developed and tested for near-surface applications during the late 1990s [9]. Land streamers, that towed arrays or spreads, have primarily been designed and tested for applications of so called continuous seismic profiling.…”
Section: Introductionmentioning
confidence: 99%